(untitled) (Al-Qamar, 2023)
Terrorism and radicalism have kept Pakistan in turmoil for decades that induced immense socio-economic harm to the country. The persistent challenge has brought about elevation in casualties, dissolutions of government and worsen law and order scenarios. Till present, the governments have been unable to root out the extremist elements from the society. This paper offers outright approach to comprehend these defies. The paper considered multifaceted elements; such as; scarcity of education, political stability, sectarianism, destitution etc. as a core for the rise of extremism. Besides, Afghanistan being the neighboring country to Pakistan has served as a sanctuary for extremist groups. Thence, Pakistan has to deal with the national and international terrorist groups. This study does the appraisal of the endeavors made by the government for hindering the terrorism. So far, the chief government strategy has been to launch military action, terrorism prevention plans and dialogue against terrorist and extremist groups that caused soaring number of civilian casualties and remained in vain to get away with these social evil. The paper adopts comprehensive ground to address the problem under study. The factors viz a viz; social reforms, economic prosperity and political stability are true remedies to defies. But, these remedies could only been effective if civil society, government in power and international stakeholders will work together for pragmatic resolutions. The paper argues that peace and instability could be happen in a country through a comprehensive approach towards the matter.